Childhood maltreatment must lead to hate? The relation between childhood maltreatment and social mindfulness among college students: the roles of self-compassion, shyness and hostile attribution bias - Wang, XiaoYi; Yang, GuangLan; Meng, WeiJie (Frontiers in Psychology, 2025)
BackgroundChildhood maltreatment represents a significant distal risk factor for the social adaptation and development of children and adolescents. However, the impact of childhood maltreatment on individuals’ social mindfulness—an emerging form of “effortless” prosocial behavior—remains largely unexplored.ObjectiveTo address the gap in understanding the relationship between childhood maltreatment and social mindfulness, To address the gap in understanding the relationship between childhood maltreatment and social mindfulness, we conducted a cross-sectional study to clarify their association and explore potential influencing factors.MethodsIn this study, 611 undergraduates were surveyed to complete a series of questionnaires including Childhood Maltreatment questionnaire-28 item Short Form(CTQ-SF), 17-item Social Mindfulness Self-report Scale(SMSRS), Shyness Scale, Chinese Version of Word Sentence Association Paradigm for Hostility Scale(CV-WSAP-Hostility), Chinese Version of Self-Compassion Scale(CV-SCS). And a moderated mediation model was constructed based on the data results.ResultsChildhood maltreatment negatively predicts social mindfulness and exerts its influence through self-compassion as a mediator. Additionally, shyness and hostile attribution bias (HAB) were found to have significant independent and interactive moderating effects. Specifically, the negative impact of childhood maltreatment on self-compassion and social mindfulness diminished as levels of both shyness and HAB increased.ConclusionThis study demonstrates that the design of intervention programs for individuals with childhood maltreatment should fully consider the “dual-edged sword” effects of their shy personality traits and HAB and the potential for iatrogenic effects.